Variotherm assisted precision injection molding of plastic optical lenses based on improved cooling stage control model - Yuwang Hu; Changxi Xue (Scientific Reports)
Abstract Precision injection-molded plastic optical lenses are extensively utilized in imaging optical systems. The residual stress and surface deformation produced during the injection molding of plastic optical lenses will immediately result in impairments in imaging quality. Conventional injection molding enhances molding quality by the optimization of process parameters, necessitating increased raw materials and multiple procedures, but it still fails to produce satisfactory results. This study proposed a variotherm assisted precision injection molding method based on an improved cooling control model. The cooling phase of variotherm assisted injection molding is controlled by determining the cooling time according to the thickness distribution derived from the surface equation of the plastic optical lens, achieving optimisation of residual stress and deformation. The residual stress and deformation of a precision injection molded aspherical plastic optical lens for imaging optical systems were studied through simulation and experimentation under different maximum and minimum temperature and cooling time conditions. The results indicate that the simulation outcomes for residual stress and deformation align with the experimental data trends, suggesting that the proposed method can further minimize the residual stress and deformation inherent in traditional variotherm assisted forming techniques.